PETROGENESIS OF THE DAR'YA ALKALINE COMPLEX IN THE KETKAP-YUNA MAGMATIC PROVINCE OF ALDAN - Polin V.F.; Sakhno V.G.; Solyanik A.N. (My University, 2004)
The association of granitoids and alkaline felsic rocks is widespread at the southern margin of the Aldan Shield. Interest in these rocks has been caused by the contrasting coexistence of sodic subalkaline (hereafter, high-Na) and potassic alkaline and subalkaline (hereafter, high-K) varieties, as well as by the low abundance and insufficient knowledge of high-K rocks. In the light of potential use of these rocks as alumina and potassium raw material, the origin of alkaline felsic rocks with variable K and Na contents should be regarded as an important theoretical and applied problem. We studied this rock association in the Ketkap-Yuna magmatic province in the southeastern Aldan Shield. In this work, the Dar'ya alkali syenite intrusive complex is considered a typical rock association of this province.